To understand or not to understand: This is the problem - Tan, Makbule Neslişah; Limnili, Gizem; Yıldırım, Ediz; Güldal, Azize Dilek (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The aim of the study was to evaluate the level of readability of the informed consent used before colonoscopy in a university hospital by different methods, and to investigate related sociodemographic variables. Materials and Methods: This descriptive, cross-sectional study included 211 subjects aged over 18. Three different measurement tools were used to evaluate the level of readability of the informed consent: The Cloze Readability Procedure, the Flesch’s readability formula adapted to Turkish by Atesman, and the readability formula developed by Cetinkaya and Uzun. Results: The readability scores of the text, calculated according to Atesman’s formula, the Cetinkaya-Uzun, and Cloze Readability Procedure were 50.183 (the average level of difficulty), 31.021 (frustration level), and 26.68 (frustration level), respectively. The informed consent was found to be appropriate for individuals educated at the grade level 10 and above. The following participants were found to have significantly higher scores: educated above high school; reading books, magazines, digital media, and printed media every day or every other day; and previously informed about colonoscopy. Conclusion: Within the framework of a colon cancer screening program conducted by the Public Health Institution of Turkey, individuals who tested positive were subjected to the colonoscopy procedure, if necessary. This increases the importance of the informed consent form used prior to the colonoscopy procedure. The patients and/or patients’ relatives who are at the frustration level of reading ability would have problems in reading and comprehending the text. The Cloze Test Procedure might be used in examining problematic consent forms. Cite this article as: Tan MN, Limnili G, Yıldırım E, Güldal AD. To understand or not to understand: This is the problem. Turk J Gastroenterol 2018; 29: 642-9.